Comparison of Efficacy of Ferric Carboxymaltose versus Iron Sucrose Complex for the Treatment of Iron Deficiency Anemia in Pregnancy: Ferric Carboxymaltose versus Iron Sucrose Complex for Iron Deficiency Anemia in Pregnancy - Javed, Florentina Prastish; Kanwal, Sumaira; Khan, Ayesha Azhar; Baig, Asma Amin; Rabeet, Muhammad; Qurshi, Muhammad Owais; Raza, Hafiz Muhammad Zeeshan; Arif, Muhammad Imran (Pakistan Journal of Health Sciences, 2026)
During pregnancy, iron deficiency anemia (IDA) is a common complication that exposes both the mother and fetus to a lot of risks. Objectives: To compare intravenous ferric carboxymaltose (FCM) versus iron sucrose in the treatment of moderate to severe anemia in pregnant women. Methods: This quasi-experimental study was conducted in a tertiary care hospital in Lahore, which registered 62 pregnant women having 16-34 weeks of gestation and hemoglobin levels of 7-9 g/dl. The participants were randomly divided into two groups, with intravenous FCM in one of them and the other without. The level of base hemoglobin and post-treatment were taken three weeks after the completion. There was also the evaluation of effectiveness and adverse impacts. Results: The average basal hemoglobin was 7.88 ± 0.42 g/dl. The levels after treatment were significantly higher in the FCM group (10.93 ± 0.63 g/dl) compared to the IS group (9.98 ± 0.51 g/dl), with an increase in statistically significant HB (p<0.001). The efficacy was reported in 87.1% of patients treated with FCM versus 38.7% in the SI group. The adverse effects were remarkably lower in the FCM group (19.4%) compared to IS (61.3%) (p=0.001). Although multiparous women had significantly lower basal HB, both parity groups showed similar responses to treatment. Conclusions: Ferric carboxymaltose demonstrated superior efficacy and tolerability compared to iron sucrose in the first leg during pregnancy. Its ability to achieve rapid HB correction with fewer side effects supports its consideration as preferred intravenous iron therapy.